32 Role of adjuvant external beam radiotherapy in stage ii endometrial cancer: a systematic review and meta-analysis. (18th September 2019) - Narasimhulu, D; Cope, AG; Petersen, IA; Cliby, WA; Langstraat, CL; Glaser, GE; Kumar, A; Cappuccio, S; Mariani, A
Abstract : Objectives: To summarize the evidence on adjuvant postoperative external beam radiotherapy (EBRT) when compared to vaginal brachytherapy (VBT) alone on survival and recurrence in women with stage II endometrial cancer (EC) defined by cervical stromal invasion. Methods: We searched MEDLINE, EMBASE, CENTRAL and Scopus through January 2019 for studies evaluating EBRT±VBT and VBT alone in stage II EC. Study selection, assessment and data abstraction were performed in duplicate. Random-effects models were used to synthesize quantitative data. Results: Fifteen cohort studies reporting data for 1070 women were included. Subgroup analysis by pelvic lymph node evaluation (sampling or full dissection) status (PLNE) was performed. We observed a statistically significant reduction in local recurrence with EBRT±VBT when compared to VBT alone (12 studies, 889 patients, OR:0.34, 95%CI:0.16–0.72, I2=0%) for women with stage II EC regardless of PLNE (figure 1 ). EBRT±VBT was associated with statistically significant reduction in mortality compared to VBT only for the subgroup who underwent PLNE (2 studies, 252 patients, OR:0.41, 95%CI:0.17–0.99, I2=0%). It was not possible to evaluate the additional morbidity with EBRT and benefit of chemotherapy in this population. Conclusions: EBRT±VBT resulted in decreased local recurrence for stage II EC regardless of PLNE status and a survival benefit only for the subgroup that underwent PLNE. These conclusions are based on observational studies warranting limited certainty. However, given the lack of, and limited prospect of acquiring prospective data in the near future, EBRT±VBT must be considered in all patients with stage II EC.